Properties of Syrian Basalt Continuous Fibers and Yarns "SBCF", their Tests (Damascus University Journal for engineering sciences, 2024)
Basalt fibers and yarns resulting from the melting of natural basalt rocks at high temperatures ranging from (1450-1600 C˚) compared to other synthetic fibers such as: (carbon fibers, glass fibers, asbestos fibers, etc.) is the mostpromising future material for many applications. Various (civil construction, concrete, facilities, automobile industry, electricity and electronics, chemical and petrochemical industry, home appliance services, pipelines, port, offshore platforms, agriculture, power plants, etc.) Its costs on the one hand, and its distinctive technical and technical characteristics on the other, in addition to the daily increase in environmental protection requirements. Therefore, this study came to shed light on the properties of these fibers and to clarify the technology of their manufacture.This study, according to the researcher's knowledge, is one of the first studies to study the properties of Syrian continuous basalt fibers and yarns. The tensile test for Syrian basalt ropes of different diameters (5 mm and 4 mm) has also been described, as much as possible, to be a starting point for the rest of the researchers in this field in order to benefit from it and work on it. to be developed and described more accurately.
Keywords: basalt rocks; Syrian basalt continuous fibers (BCF); basalt yarns (roving); basalt ropes; tensile test; (EDX) test